Variable effects of wolves on niche breadth and density of intraguild competitors. Issue 2 (9th February 2022) - Fowler, Nicholas L.; Petroelje, Tyler R.; Kautz, Todd M.; Svoboda, Nathan J.; Duquette, Jared F.; Kellner, Kenneth F.; Beyer, Dean E.; Belant, Jerrold L.
Abstract: The parallel niche release hypothesis (PNR) indicates that reduced competition with dominant competitors results in greater density and niche breadth of subordinate competitors and which may support an adaptive advantage. We assessed support for the PNR by evaluating relationships between variation in niche breadth and intra‐ and interspecific density (an index of competition) of wolves ( Canis lupus ) coyotes ( C. latrans ), and bobcats ( Lynx rufus ). We estimated population density (wolf track surveys, coyote howl surveys, and bobcat hair snare surveys) and variability in space use (50% core autocorrelated kernel density home range estimators), temporal activity (hourly and overnight speed), and dietary (isotopic δ 13 C and δ 15 N) niche breadth of each species across three areas of varying wolf density in the Upper Peninsula of Michigan, USA, 2010–2019. Densities of wolves and coyotes were inversely related, and increased variability in space use, temporal activity, and dietary niche breadth of coyotes was associated with increased coyote density and decreased wolf density supporting the PNR. Variability in space use and temporal activity of wolves and dietary niche breadth of bobcats also increased with increased intraspecific density supporting the PNR. Through demonstrating decreased competition between wolves and coyotes and increased coyote niche breadth and density, our study provides multidimensional support for the PNR. Knowledge of the relationship between niche breadth and population density can inform our understanding of the role of competition in shaping the realized niche of species. Abstract : Locations of study areas (ESC, CF, and SM) used to assess patterns in niche variability of gray wolves ( Canis lupus ), coyotes ( C. latrans ), and bobcats ( Lynx rufus ), Upper Peninsula of Michigan, USA, 2010–2019.